1990
DOI: 10.1093/brain/113.2.303
|View full text |Cite
|
Sign up to set email alerts
|

The Corticospinal Tracts in Man

Abstract: The course, location and relations of the corticospinal tracts within the spinal cord of man are demonstrated on the basis of cases with lesions above the spinal cord restricted to the corticospinal tracts, of motor neuron disease, and of anterolateral cordotomies; control cases were of normal spinal cords. The following features of the lateral corticospinal tract are emphasized in the cervical cord: (1) the large extent of the white matter of the cord covered by the tract, and the anterior extent of the tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(58 citation statements)
references
References 0 publications
3
46
2
Order By: Relevance
“…However this finding is at variance with the results of a study of autopsy brains that failed to show any consistent relation between the volume of motor cortex (area 4) and hand preference (10). In addition, in the latter study, the authors found no asymmetry at other levels of the sensorimotor system such as the medulla or spinal cord although such asymmetries have been reported by others (22)(23)(24). In an effort to account for the lack of structural asymmetry at the level of the motor cortex, White et al (10) have suggested that structural changes in the primary motor cortex contralateral to the dominant hand may be balanced by structural changes associated with ''less obvious capabilities'' than handedness in the motor cortex contralateral to the nondominant hand.…”
Section: Discussioncontrasting
confidence: 64%
“…However this finding is at variance with the results of a study of autopsy brains that failed to show any consistent relation between the volume of motor cortex (area 4) and hand preference (10). In addition, in the latter study, the authors found no asymmetry at other levels of the sensorimotor system such as the medulla or spinal cord although such asymmetries have been reported by others (22)(23)(24). In an effort to account for the lack of structural asymmetry at the level of the motor cortex, White et al (10) have suggested that structural changes in the primary motor cortex contralateral to the dominant hand may be balanced by structural changes associated with ''less obvious capabilities'' than handedness in the motor cortex contralateral to the nondominant hand.…”
Section: Discussioncontrasting
confidence: 64%
“…The reason for this is felt to be the predominance of contralateral corticospinal projections, which arise from the cortical regions of the brain and decussate in the caudal medulla before traveling to the spinal cord [1]. While not all fibers decussate, 70-90% of them do, resulting in this ‘crossed' clinical finding [2]. Prior neuroanatomical studies have firmly supported the notion that the primary motor cortex predominantly innervates the contralateral half of the body [3].…”
Section: Introductionmentioning
confidence: 99%
“…For Davidoff, 1 the function of uncrossed pyramidal axons remains unknown, but others 4 suggest that it exerts some control on bilateral proximal limb movements. The presence of functional ipsilateral corticospinal connections appears to be a normal state in infants and children aged Ͻ10 years, 5 but their presence in adult humans is still debated.…”
mentioning
confidence: 99%